Individual Differences In Gaze Patterns For Web Search - Dumais, Susan; Buscher, Georg; Cutrell, Ed (Proceeding of the third symposium on Information Interaction in Context, 2010)
We investigate how people interact with Web search engine result pages using eye-tracking, to provide a detailed understanding of the patterns of user attention. Previous research has examined the visual attention devoted to the 10 organic search results, and we extend this by also examining how gaze is distributed across other components of contemporary search engines, such as ads and related searches. This provides insights about searcher’s interactions with the “whole page”, and not just individual components. In addition, we used clustering techniques to identify groups of individuals, with distinct gaze patterns. The groups varied in how exhaustively they examined the search results and in what regions of the search result page they paid most attention to (organic results vs. ads). These results further our understanding of how attention is distributed across increasingly complex search result pages, and how individuals exhibit distinct patterns of attention and interaction.